Human talent management models: A theoretical review for organizational development - Frías Pérez , Edisson Andrés (2025)
Human talent management has established itself as a critical factor for the success and sustainability of organizations. The objective of this article is to examine the main models that support strategic human talent management, emphasizing its evolution from traditional administration to contemporary approaches. The article uses a qualitative, analytical, and documentary approach. A literature review was conducted, prioritizing articles indexed in Scopus and Web of Science. The results of the analysis highlight the role of strategic planning, competency-based training, motivation, organizational culture, and institutional commitment as fundamental pillars for organizational development and sustainability. It is concluded that the adoption of systemic approaches, focused on comprehensive human development and aligned with corporate strategic objectives, generates a balance between productivity and collective well-being and responds to the challenges of the changing environment